Invasion genetics: Lessons from a ubiquitous bird, the house sparrow Passer domesticus. Issue 3 (1st June 2015) - Liebl, Andrea L.; Schrey, Aaron W.; Andrew, Samuel C.; Sheldon, Elizabeth L.; Griffith, Simon C.
Abstract: Following an introduction, non-native species are exposed to environments that differ from those found in their native range; further, as these non-native species expand beyond the site of introduction, they must constantly adapt to novel environments. Although introduced species are present across most ecosystems, few species have successfully established themselves on a truly global scale. One such species, the house sparrow Passer domesticus, is now one of the world's most broadly distributed vertebrate species and has been introduced to a great part of its current range. To date, work on four continents suggests both genetic and phenotypic variation exists between native and introduced ranges. As such, house sparrows represent an excellent opportunity to study adaptations to novel environments and how these adaptations are derived. The global distribution of this species and the multiple independent introductions to geographically isolated sites allow researchers to ask questions regarding genetic variation and adaptation on a global scale. Here, we summarize the molecular studies of invasive house sparrows from the earliest work using allozymes through more recent work on epigenetics; using these studies, we discuss patterns of dispersal of this species. We then discuss future directions in techniques (e.g. next generation sequencing) and how they will provide new insight into questions that are fundamental to invasion biology. Finally, we discuss how continued research on the house sparrow in light of these genetic changes and adaptations will elucidate answers of adaptation, invasion biology, range expansion, and resilience in vertebrate systems generally.